A global perspective of government initiatives to support higher education during the COVID-19 pandemic: A systematic review of literature - Asad Abbas; Anil Yasin Ar; Samira Hosseini (Research in Globalization, 2024)
The coronavirus disease 2019 (COVID-19) pandemic crisis has forced higher education institutions (HEIs) to develop preventative measures in compliance with national and international policies. In varying degrees, some of these measures cause disruptions in their way of offering educational services, whereas others enable them to continue offering their services to students. By surveying the relevant literature based on the Scopus database between 2020 and 2022 (inclusive), this study provides insight into governments' educational policies during the COVID-19 pandemic and their implications. For data analysis, the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) is utilized to explore government contingent policies related to higher education. R-studio is employed for thematic mapping based on keywords and abstracts from selected papers to integrate and present themes and current trends. Based on the analyzed results of 43 papers, it is concluded that during the COVID-19 pandemic, government policies were strongly associated with higher education digital transformation. Moreover, the government mainly plays a critical role in restructuring budgets, building infrastructures, and establishing social initiatives to support HEIs and students during the crisis. For the mentioned reasons, this study indicates the importance of governments' role and their policymaking strategies in terms of faculty development program initiations, funding and budget structure, administration, support for upgrading the existing information technology infrastructure, and establishment of new digital platforms to mitigate health risks while ensuring desirable learning outcomes through digital means during health crisis.
Keywords: 330; COVID-19; Digital transformation; Educational innovation; Government policies; Higher education; PRISMA